2022
DOI: 10.1103/physrevd.105.035026
|View full text |Cite
|
Sign up to set email alerts
|

Minimal SU(6) gauge-Higgs grand unification

Abstract: We present a minimal viable Gauge-Higgs Grand Unification scenario in warped space based on a SU (6) bulk symmetry -unifying the gauge symmetries of the SM and their breaking sector. We show how the issue of light exotic new states is eliminated by appropriately breaking the gauge symmetry on the UV and IR boundaries by either brane scalars or gauge boundary conditions. The SM fermion spectrum is naturally reproduced including Dirac neutrinos and we compute the Higgs potential at one-loop, finding easily solut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Finally, identifying the (20 AL , 20 R ) variant as the most promising model, we presented a numerical analysis and showed that the Z 2 SNR setup emerges with natural values of the model coefficients, matching all criteria identified in the EFT analysis. It would be interesting to explore if the found thermal history could also emerge in other motivated models beyond the SM, like in the recently proposed model of SU (6) Gauge-Higgs Grand Unification with an extra scalar singlet [35,36], or in further models with extended scalar sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, identifying the (20 AL , 20 R ) variant as the most promising model, we presented a numerical analysis and showed that the Z 2 SNR setup emerges with natural values of the model coefficients, matching all criteria identified in the EFT analysis. It would be interesting to explore if the found thermal history could also emerge in other motivated models beyond the SM, like in the recently proposed model of SU (6) Gauge-Higgs Grand Unification with an extra scalar singlet [35,36], or in further models with extended scalar sectors.…”
Section: Discussionmentioning
confidence: 99%
“…where 𝑧 ∈ [𝑅, 𝑅 ], and 𝑅 ∼ 1/𝑀 PL (𝑅 ∼ 1/TeV) is the position of the UV (IR) brane, addressing the HP. To arrive at a low-energy theory that resembles the Standard Model (SM), the 𝑆𝑈 (6) bulk symmetry is broken to subgroups 𝐻 0 and 𝐻 1 on the UV and the IR branes, respectively, by gauge boundary conditions (BCs), inducing [14] 𝑆𝑈 (6) → 𝑆𝑈 (5) ≡ 𝐻 0 ,…”
Section: Modelmentioning
confidence: 99%
“…From a different point of view, such models can be seen as a natural extension of GHU and the pNGB-Higgs, since they employ a set of generators of an enlarged symmetry, characteristic of these frameworks (see [16]), to realize a GUT. Finally, the construction [14] also solves the other mentioned issues of GUTs, i.e., proton decay and doublet-triplet degeneracy and is in principle accessible at colliders. All of this is achieved without the emergence of problematic ultra-light exotic states and with a Higgs mass residing easily at 𝑚 ℎ = 125 GeV, while keeping the concept of minimality -overcoming difficulties of similar proposals [17][18][19][20][21][22][23][24][25][26][27], which for example require more dimensions or large (ad-hoc) extensions of the matter sectors to become viable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the 𝑅 𝐷 ( * ) anomalies could also be tackled in CH via leptoquark states[78][79][80], see also[81,82].…”
mentioning
confidence: 99%